2022
DOI: 10.1097/apo.0000000000000489
|View full text |Cite
|
Sign up to set email alerts
|

China Turns to School Reform to Control the Myopia Epidemic: A Narrative Review

Abstract: Myopia is now a major public health issue in parts of East and Southeast Asia, including mainland China. In this region, around 80% of students completing 12 years of school education are now myopic, and from 10% to 20% have high myopia in excess of À6D. Interventions to prevent the onset of myopia based on increasing time outdoors have now been implemented at a system-wide scale in Chinese Taipei (Taiwan) and Singapore with some success, but the prevalence of myopia still remains high by international standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 79 publications
1
36
0
Order By: Relevance
“…This could be explained by the hyperopic shift caused by decreased lens refractive power, flattened corneal curvature as well as displacements of the lens with age. Myopia was positively correlated with education level in the current study and previous large cohort studies,27–29 which could be attributed to the reduction of time spent outdoors with increasing educational pressures 30,31. Recent mendelian randomization studies showed that every additional year of education was associated with a more myopic RE of 0.27 D per year 32.…”
Section: Discussionsupporting
confidence: 69%
“…This could be explained by the hyperopic shift caused by decreased lens refractive power, flattened corneal curvature as well as displacements of the lens with age. Myopia was positively correlated with education level in the current study and previous large cohort studies,27–29 which could be attributed to the reduction of time spent outdoors with increasing educational pressures 30,31. Recent mendelian randomization studies showed that every additional year of education was associated with a more myopic RE of 0.27 D per year 32.…”
Section: Discussionsupporting
confidence: 69%
“…In recent years the search for a treatment that will halt myopia progression has yielded several options. Low-concentrated atropine, orthokeratology, bifocal or progressive addition ophthalmic lenses, and soft multifocal centerdistance-peripheral-blur contact lenses have all shown effectivity [12,13,18]. This article will discuss peripheral defocus as it pertains to myopia progression and the optical methods devised to date in an attempt to control it.…”
Section: Contributing Factors To Myopia Progressionmentioning
confidence: 99%
“…Schools play an important role in conducting organized outdoor activities, not limited to outdoor education initiatives, or physically conducting lessons outdoors. In China, efforts have been made to structure and enforce learning breaks in a manner that would better allow children to get outdoors between classes, in addition to the implementation of daily after-school and outdoor holiday programs across public schools 80. As myopia prevention efforts are often closely integrated within school systems in several Asian countries,81 there needs to be a balance between restriction measures and the ability to perform outdoor activities while safe distancing.…”
Section: Discussionmentioning
confidence: 99%